DETERMINANTS OF STOCK RETURNS AND THEIR IMPLICATIONS FOR PRICE BOOK VALUE - Sukirno, Sukirno; Putri, Titania Saskia (Yayasan Education and Social Center, 2024)
This research aims to analyze the influence of the Current Ratio and Debt Equity Ratio on Stock Returns with Return on Assets as a moderating variable on the Southeast Asian Stock Exchange. The data collected is secondary data with a documentation method in the form of the company's annual report. The analytical tool used to test the hypothesis is SPSS 26. The sampling method used in this research uses a purposive sampling technique and 11 company samples were obtained from a population of 225 companies. The analysis techniques used are multiple linear regression analysis, moderating regression analysis, partial tests and simultaneous tests. The partial research results conclude that the Current Ratio has no effect on Stock Returns, the Debt to Equity Ratio has no effect on Stock Returns. The research results simultaneously show that the Current Ratio and Debt Equity Ratio together have a significant effect on Stock Returns. In moderation, Return on Assets is able to moderate the relationship between the Current Ratio to Stock Returns and the Debt Equity Ratio to Stock Returns. Price Book to Value has a positive impact on Stock Returns